The Effect Of Profitability, Company Complexity, Company Risk And Board Of Commissioners On Audit Fees - Rimet, Rimet; Syakirin, Fakhrul (Jurnal Rumpun Ilmu Ekonomi, 2024)
This study aims to determine the effect of profitability, company complexity, company risk, and board of commissioners on audit fees in good and beverages sub-sector companies in the consumer goods sector listed on the Indonesia Stock Exchange. The sample of this study was obtained using purposive sampling technique, so that 45 samples were obtained with the research period 2020-2022. Data analysis using the classical assumption test and hypothesis testing using panel data regression analysis using the eviews version 12 tool. The results of this study indicate that company complexity and board of commissioners have an effect on audit fees, while profitability and company risk have no effect on audit fees. From the results of the study also obtained the coefficient of determination (R2) with a value of 0.49 means that the magnitude of the influence of profitability, company complexity, company risk, and board of commissioners is 49%.